DNA Polymerase II (polB) Is Involved in a New DNA Repair Pathway for DNA Interstrand Cross-Links in Escherichia coli - Berardini, Mark (American Society for Microbiology, 1999)
DNA-DNA interstrand cross-links are the cytotoxic lesions for many chemotherapeutic agents. A plasmid with a single nitrogen mustard (HN2) interstrand cross-link (inter-HN2-pTZSV28) was constructed and transformed into Escherichia coli, and its replication efficiency (RE = [number of transformants from inter-HN2-pTZSV28]/[number of transformants from control]) was determined to be ∼0.6. Previous work showed that RE was high because the cross-link was repaired by a pathway involving nucleotide excision repair (NER) but not recombination. (In fact, recombination was precluded because the cells do not receive lesion-free homologous DNA.) Herein, DNA polymerase II is shown to be in this new pathway, since the replication efficiency (RE) is higher in a polB(+) (∼0.6) than in a ΔpolB (∼0.1) strain. Complementation with a polB(+)-containing plasmid restores RE to wild-type levels, which corroborates this conclusion. In separate experiments, E. coli was treated with HN2, and the relative sensitivity to killing was found to be as follows: wild type < polB < recA < polB recA ∼ uvrA. Because cells deficient in either recombination (recA) or DNA polymerase II (polB) are hypersensitive to nitrogen mustard killing, E. coli appears to have two pathways for cross-link repair: an NER/recombination pathway (which is possible when the cross-links are formed in cells where recombination can occur because there are multiple copies of the genome) and an NER/DNA polymerase II pathway. Furthermore, these results show that some cross-links are uniquely repaired by each pathway. This represents one of the first clearly defined pathway in which DNA polymerase II plays a role in E. coli. It remains to be determined why this new pathway prefers DNA polymerase II and why there are two pathways to repair cross-links.